Electric Power Applications - Barrero, Federico; Bermúdez, Mario (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The continuing trend toward greater electrification in consumer, commercial, industrial, and transportation applications promises a dynamic and increasingly important role for power electronics. The term 'power electronics' refers to electric and electronic circuits whose primary function is to process energy. The growing penetration of power electronics in energy systems requires attention, with its principal challenges being cost reduction and reliability. Power electronic systems are indispensable parts of modern engineering applications, covering a wide range of engineering branches. This Special Issue focuses on modern applications of electricity, power electronics converters, and electric motor drives.